Surgical treatment of acute infectious purpura fulminans in neonates - Paola Parisi; Diego Ribuffo (Hygeia Press di Corridori Marinella, 2022)
Neonatal purpura fulminans (NPF) is a rare entity due to a deficiency in anticoagulant protein C or S that leads to the development of disseminated intravascular coagulation with formation of microvascular thrombi and skin and soft tissue necrosis. Three forms of NPF are described: congenital, infectious and idiopathic. Acute infectious purpura fulminans (AIPF) is related to sepsis. Group B Streptococcus spp. is the most frequent pathogen involved in the development of AIPF in newborns. The clinical severity varies according to the underlying cause. The mortality rate of AIPF ranges from 10% to 50%. Limbs are involved more frequently than other areas. Skin lesions may present early as petechial rashes, which rapidly progress to larger ecchymoses. Later in the course, hemorrhagic bullae may form, which contribute to the classic hard eschars characteristic of NPF. Differential diagnosis with necrotizing fasciitis should be performed. Treatment of NPF should be multidisciplinary. Plastic surgeons are frequently involved in the management of soft tissue defects. Surgical treatment consists in early debridement or amputation in more critical cases and subsequent reconstruction by using skin grafts, pedicled or free flaps. Medical research is now focused on bioengineering solutions that can provide better aesthetic and functional outcomes while minimizing surgical sequelae. The aim of this editorial is to present the available options and the state-of-the-art research and scientific advances in local wound care and surgical management of AIPF.